Centro de tecnificación para pequeños caficultores del municipio de Garzón, Huila - Puerta Franco, Omar Santiago (Universidad Antonio Nariño, 2022)
Coffee is one of the most important agricultural matters of Colombia, being the first product in this field in export, which has mean the livelihood of thousands of families in the territory they live of this work, however, there are many problems that this sector presents, starting with the modernization processes in the transformation of the coffee bean, which has fallen short by the lack of appropriate spaces to implement a process that is more sustainable, leading to Colombia only export raw materials, mainly in parchment coffee, without giving small coffee growers the opportunity to develop a completely finished product.